2015
DOI: 10.1111/hepr.12468
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of improved prognosis between hepatitis B‐ and hepatitis C‐related hepatocellular carcinoma

Abstract: Aim: Treatment strategies for hepatocellular carcinoma (HCC) have been advanced. The aim of this study was to compare the change of the prognosis between hepatitis B-related HCC (B-HCC) and hepatitis C-related HCC (C-HCC) in the last two decades. Results: Two (11%), 24 (49%) and 80 (82%) B-HCC patients received nucleoside/nucleotide analogs during the follow-up period in cohorts 1-3, respectively. Among them 1, 18 and 62 patients achieved viral remission, respectively. Thirty-four (18%), 35 (8%) and 84 (14%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Interestingly, the HCC risk gene signature quantitatively depicted the relative risk status of the liver according to etiology (Figure 1A). HBV-infected liver showed relatively lower risk status (p<0.001, Kolmogorov-Smirnov test) consistent with the clinical observation that HBV-related HCC is associated with less frequent post-surgical/ablative HCC development compared to HCV in both Western and Eastern patient cohorts (Franssen et al, 2014; Minami et al, 2015). In contrast, NAFLD/NASH-affected livers accumulated on the higher risk side (p<0.001) despite the lowest frequency of established cirrhosis (23% in NAFLD, 21% in NASH).…”
Section: Resultssupporting
confidence: 82%
“…Interestingly, the HCC risk gene signature quantitatively depicted the relative risk status of the liver according to etiology (Figure 1A). HBV-infected liver showed relatively lower risk status (p<0.001, Kolmogorov-Smirnov test) consistent with the clinical observation that HBV-related HCC is associated with less frequent post-surgical/ablative HCC development compared to HCV in both Western and Eastern patient cohorts (Franssen et al, 2014; Minami et al, 2015). In contrast, NAFLD/NASH-affected livers accumulated on the higher risk side (p<0.001) despite the lowest frequency of established cirrhosis (23% in NAFLD, 21% in NASH).…”
Section: Resultssupporting
confidence: 82%
“…Some studies have also suggested that IFN therapy can reduce the risk of HCC [4][5][6]. However, until recently, IFN-containing regimens have shown unsatisfactory SVR rates in patients with advanced fibrosis or cirrhosis due to lower dose intensity and adherence as a result of more severe adverse effects in these patients [7][8][9]. Currently, IFN-free, all-oral regimens with direct-acting antivirals (DAAs) have shown nearly 100% SVR rates in patients not suitable for IFN-containing regimens [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding patient characteristics, only HCVAb positivity was a negative predictor of liver volume recovery, with marginal significance. This could be because HCV‐positive patients have incurred more liver damage due to chronic hepatitis . Regarding tumor‐related factors, tumor size was not associated with liver volume recovery.…”
Section: Discussionmentioning
confidence: 96%